OPTIMALISASI MODEL BISNIS UMKM BERBASIS DIGITAL UNTUK MENINGKATKAN DAYA SAING DI ERA INDUSTRI 4.0 - Muhamad Febrianto; Nashran Azizan, Maulana Arafat Lubis (Adiba Aisha Amira, 2025)
The purpose of this study is to see how to Optimize Digital-Based MSME Business Models to Increase Competitiveness in the Industrial Era 4.0. The form of this research is descriptive, analytical, and critical. Therefore, the author can elaborate comprehensively. In this study, the author optimally uses two data sources related to this research, namely. Primary data sources and secondary data sources. The results of this research are By utilizing e-commerce, social media, digital payments, and other technologies, MSMEs can increase competitiveness in the Industry 4.0 era must be able to adopt technology, increase innovation, and strengthen digital strategies. With the right approach, MSMEs can not only compete in the local market but also penetrate the global market.